(untitled) (Vietnam Journal of Community Medicine, 2023)
Objectives: To describe the quality of life score of a 6-14 year old pediatric patient with allergic rhinitis. Methods: A cross-sectional descriptive study on 855 children 6-14 years old with allergic rhinitis, using the PRQLQ scale. Results: The average total quality of life score according to the PRQLQ scale was 77.44±19.32, of which the highest was 125 points and the lowest was 14 points. In addition, there was a statistically significant relationship between the severity of the disease over time and the severity of the quality of life score (p<0.005). Conclusion: Children with persistent, severe allergic rhinitis affect their quality of life more than children with intermittent, mild allergic rhinitis.